2010
DOI: 10.1787/5km91nkdt6d6-en
|View full text |Cite
|
Sign up to set email alerts
|

Competitiveness, Productivity and Efficiency in the Agricultural and Agri-Food Sectors

Abstract: This report reviews the literature on competitiveness, productivity and efficiency in the agricultural and agri-food sectors. It clarifies concepts and terminology used in this area, and provides a critical assessment of approaches and indicators used in the literature to measure competitiveness, productivity and efficiency at sectoral and farm levels. It also discusses recent findings on productivity growth, changes in relative competitiveness between sub-sectors and countries, and determinants of competitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(112 citation statements)
references
References 100 publications
0
84
0
15
Order By: Relevance
“…This efficiency can be connected up to the productivity of the business's factors of production (Latruffe, 2010). One definition of productivity is the capacity of production factors to produce goods and services.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This efficiency can be connected up to the productivity of the business's factors of production (Latruffe, 2010). One definition of productivity is the capacity of production factors to produce goods and services.…”
Section: Methodsmentioning
confidence: 99%
“…High productivity (high volume of a good produced for a low amount of input consumed) can be considered as high efficiency of this input. The aggregate of all outputs with the aggregate of all inputs makes it possible to calculate the wealth -or value added -created by the business in a more dynamic trend analysis of productivity (Latruffe, 2010), that is, the technical efficiency of the production system. The concept of value added.…”
Section: Methodsmentioning
confidence: 99%
“…The NEI is the difference between a sector's exports and imports divided by the total value of trade (Banterle and Carraresi, 2007). The GL indicator assesses the health of exports by accounting for the fact that a product is often exported and imported at the same time (Latruffe, 2010). It measures intra and inter-industry trade for a given product.…”
Section: Methodsmentioning
confidence: 99%
“…A study has shown that productivity and efficiency are the indexes of competitiveness [14]. Another studies also stated that productivity and efficiency are the most reliable measurest of competitiveness [15].…”
Section: Malmquist Productivity Index (Mpi)mentioning
confidence: 99%